FEATURES OF THE CONCEPT AND CONTENT OF PUBLIC SECURITY - Muntian, Liliia (Public Administration and Regional Development, 2024)
The article analyzes the concept of public security in relation to such categories as «security», «national security», «state security», «security of society», «public order». An analysis of the scientific literature on this problem shows that in modern science there are two main approaches to understanding the phenomenon of «public security». Representatives of the first approach define public security as a social state, namely as a state of protection of the vital interests of the individual, society and the state from internal and external threats. Representatives of the second approach understand public security as a system of social relations that develop in the process of protecting the vital interests of the individual, society and the state from internal and external threats. Based on a thorough analysis of the concepts available in modern science, the author's definition of public security was formed. The important role and significance of public security in the existence of a modern state and society is emphasized, since it is this category that is the most relevant model for regulating social relations by maintaining law and order in society and the state. It is noted that public security should be considered from different points of view. First of all, as a concept that helps to reveal the meaning of the concept of security and its derivatives, as a certain state of protection of society and the state. It is emphasized that this aspect is the most important condition for establishing and maintaining law and order. It is substantiated that the use of the concept of public security leads to the emergence of certain concepts and strategies that also require thorough analysis and are a reflection of the relationship and interdependence between the development and security of society. The author draws special attention to the similarity of such concepts as public and national security. Most modern studies emphasize the fact that public security is one of the types of national security, since national security is a complex security concept and phenomenon in the context of increasing internal and external threats to the modern world.